La scène internationale : les nouveaux horizons dans Daniel Deronda de George Eliot - Stéphanie Drouet-Richet (Cahiers Victoriens et Edouardiens)
At the end of Daniel Deronda, as the hero is about to leave England so as to start a family in what is to be the new Jewish National Centre, a new perspective is created : this new horizon is that of the East. The final episode, which is a beginning as well as an ending, mirrors the whole novel, which itself harks back to George Eliot’s earlier fiction, yet is also radically different. Daniel Deronda operates on a vaster scale, following a progression from restricted microcosm to complex macrocosm, exploring new bearings on the international scene, away from the narrow concerns of the individual to the recognition of the needs of other fellow beings. Daniel Deronda is definitely a novel about borders to be crossed.